2017
DOI: 10.4254/wjh.v9.i1.64
|View full text |Cite
|
Sign up to set email alerts
|

Shear wave elastography in hepatitis C patients before and after antiviral therapy

Abstract: AIMTo investigate shear wave (SW) propagation velocity in patients with untreated hepatitis C and patients with sustained virological response (SVR).METHODSA total of 136 hepatitis C patients [85 patients who had not received antiviral therapy (naïve group) and 51 patients who had received antiviral therapy and subsequently achieved SVR of at least 24 wk (SVR group)] and 58 healthy volunteers and outpatients without liver disease (control group) underwent evaluation of liver stiffness by SW elastography (SWE).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 21 publications
2
13
1
1
Order By: Relevance
“…Furthermore, the SWV was significantly negatively correlated with Plt and Alb but significantly positively correlated with T.Bil, AST, ALT, PT, HA, IV‐c‐7S and M2BPGi. These results are consistent with previous reports and show that liver stiffness measurements are associated with several complex factors of the liver, not just fibrosis but also inflammation …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Furthermore, the SWV was significantly negatively correlated with Plt and Alb but significantly positively correlated with T.Bil, AST, ALT, PT, HA, IV‐c‐7S and M2BPGi. These results are consistent with previous reports and show that liver stiffness measurements are associated with several complex factors of the liver, not just fibrosis but also inflammation …”
Section: Discussionsupporting
confidence: 94%
“…These results are consistent with previous reports and show that liver stiffness measurements are associated with several complex factors of the liver, not just fibrosis but also inflammation. [35][36][37][38] Several limitations associated with the present study warrant discussion. First, the study included a relatively small number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with advanced liver disease have a lower response to DAA therapy . Alpha‐fetoprotein level is probably associated with liver stiffness . Therefore, AFP levels are linked to the efficacy of treatment with daclatasvir plus asunaprevir.…”
Section: Discussionsupporting
confidence: 76%
“…Because inflammation was improved at SVR24, it appears that SWE results at SVR24 provide a clear evaluation of liver fibrosis. Furthermore, a recent study suggested that SWE provides an accurate evaluation of liver fibrosis in patients who had achieved SVR [ 28 ].…”
Section: Discussionmentioning
confidence: 99%